The 2018/2019 drought in the UK: a hydrological appraisal. (10th June 2021) - Turner, S.; Barker, L. J.; Hannaford, J.; Muchan, K.; Parry, S.; Sefton, C.
Abstract : Between 2016 and 2019, the UK was in a period of prolonged dry conditions with varying spatial and temporal foci. We look at the rainfall, river flows, soil moisture and drought impacts leading up to and including the heatwave of 2018, and the following year, placing the events into historical context. Using incident data from the UK regulators, we also explore drought impacts for this period.